FAKTOR RESIKO PENYAKIT TB (TUBERKULOSIS) DI KECAMATAN KABANJAHE KABUPATEN KARO TAHUN 2021 - Tambunan, Helfi Nolia; Tanjung, Risnawaty; Sihombing, Nurmala Hayati; Sinaga, Jernita (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Tuberculosis (TB) is a direct infectious disease caused by TB (mycobactic tuberculosis) germs. The disease is still in the attention of the world and until now, there are no one neither country free from TB. Deli Serdang regency is an regency with the highest Tuberculosis case discovery in North Sumatra Province. This study was observational research with the design of study control cases, in order to determine the characteristics of the patient and the risk factor for the tuberculosis incident. The number of samples is 45 cases and 45 controls. The characteristic association and risk factors with the incidence of tuberculosis were analyzed in univariat and bivariat, Analysis is carried out using cross-con 2x2 to calculate the value of prevalen ratios and confidence values (CI). Statistical test used for analysis is chi square at the trust rate 95% (? = 5%). The results of the lighting study are obtained from the value of OR 0.348, CI 0.144 - 0.840 and p-value 0,031. Residence density obtained from the OR 0.35 CI 0.142 - 0.700 p-value 0.020 and Venting obtained from the OR 0,348 CI 0,144 – 0,840 p-value 0.031. Lighting, venting, and residence density have a relation with the incident TB in Kabanjahe District, while the variables with no relation are temperature, moisture and house floor condition.